Strategies in Managing Rapport in Classroom Discussion - Reski Reski (EDUVELOP, 2018)
ABSTRACT This paper aims to find out the strategies, applied by students in classroom interaction particularly in discussion, to maintain their interpersonal rapport as well as to enhance their rapport management with their fellow students. There are five strategies based on Spencer-Oatey (2008) that the interactants apply in social interactions. The strategies are request, compliments, apologies, gratitude and disagreement. The research is done to see whether the students realize the management of rapport in social interaction and their strategies that they would apply in classroom discussion. The research is done by using descriptive qualitative method to identify the students’ strategies in maintaining their interpersonal rapport and enhancing the rapport management with their fellow students. The data was obtained by video-recording the interactions of the students during the classroom discussions and by giving the students some questionnaires. The researcher also applied the participant observation to see the students reactions during the discussion considering that the strategies that the students apply may bring about the rapport threat and enhancement which are subjective evaluations, which depend not simply on the content of the message, but on people’s interpretations and reactions to who says what under what circumstances. The research indicates that the students’ mostly applied strategy is disagremeent and the type of the disagreement is token agreement. In other words, the students tend to hold the rapport enhancement behavior since in expressing their disagreement, they initially expressed their agreement as a token of appreciation. Keywords:classroom discussion, interpersonal rapport, rapport management, rapport orientation